IMPLEMENTATION OF MANAGEMENT FUNCTIONS IN THE NGRIPTO RARAS ART STUDIO SUKOREJO VILLAGE, PARENGAN DISCTRICT, TUBAN DISCTRICT - Yunisa, Elvajril Dhika; ., Arif Hidajad (APRON Jurnal Pemikiran Seni Pertunjukan, 2024)
Ngripto Raras Art Studio is a forum that has a function in developing the potential of human resources to shape the character of members and the surrounding community who are creative, innovative, and collaborative through art and culture. Ngripto Raras Art Studio located in Sukorejo Village, Parengan District is a studio that has excellence in organizational management in that it is a supporting factor for the development of Sukorejo Village which has been crowned as a Cultural Tourism Village. Researchers take the formulation of the problem (1) How to implement management functions (planning, organizing, mobilizing, and supervising), (2) How the results of implementing management functions through SWOT review at theNgripto RarasArt Studio Sukorejo Village, Parengan District, Tuban Regency. The theory in this study uses management theory, management functions, and Art Studio. This research uses a qualitative approach. Data collection using (1) Observation or Observation Techniques, (2) Interview Techniques, and (3) Documentation Techniques. The results of this study show thatNgripto RarasArt Studio is guided by the application of the work system to the work program as an effort to keep the process going. The implementation of management functions includes 1) Planning, as proven by work programs that can run smoothly every year, 2) Organization, as proven by an even division of labor system, , 3) Mobilization, the chairman becomes a driving force in the implementation of activities and 4) Supervision, chairman and owner of full control to supervise the running of activities. In the SWOT analysis of strengths, weaknesses, opportunities, and threats are more or less the same as the results of the application, by having strengths contained in planning that hold joint bugs that are useful for program preparation. The weakness lies in members who are still not disciplined to duty. Opportunities are obtained from the support of the surrounding community which is very high. The threat ofNgripto RarasArt Studio in its development if the Ngripto Raras Art Studio continues to lack members due to unsystematic regeneration factors, it will be a setback in the future. The need for a well-regenerated system. Keywords: Application, Management Function, Ngripto Raras Art Studio